2013
DOI: 10.1042/bj20130282
|View full text |Cite
|
Sign up to set email alerts
|

ROS inhibitor N-acetyl-L-cysteine antagonizes the activity of proteasome inhibitors

Abstract: NAC (N-acetyl-l-cysteine) is commonly used to identify and test ROS (reactive oxygen species) inducers, and to inhibit ROS. In the present study, we identified inhibition of proteasome inhibitors as a novel activity of NAC. Both NAC and catalase, another known scavenger of ROS, similarly inhibited ROS levels and apoptosis associated with H2O2. However, only NAC, and not catalase or another ROS scavenger Trolox, was able to prevent effects linked to proteasome inhibition, such as protein stabilization, apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
183
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(191 citation statements)
references
References 31 publications
8
183
0
Order By: Relevance
“…No significant increases in cell viability were noted when cells were pre-treated with Trolox. Similar results show that pre-treatment with NAC but not Trolox has an effect on activity of 1 [19]. Compound 1 is a relatively reactive compound, due to the reactive α,ÎČ-unsaturated carbonyl system contained in the piperidinone ring.…”
Section: Effect Of Pre-treatment With Antioxidants On Cellular Viabilitysupporting
confidence: 71%
See 2 more Smart Citations
“…No significant increases in cell viability were noted when cells were pre-treated with Trolox. Similar results show that pre-treatment with NAC but not Trolox has an effect on activity of 1 [19]. Compound 1 is a relatively reactive compound, due to the reactive α,ÎČ-unsaturated carbonyl system contained in the piperidinone ring.…”
Section: Effect Of Pre-treatment With Antioxidants On Cellular Viabilitysupporting
confidence: 71%
“…Trolox (100 ÎŒM and 300 ÎŒM) has been shown to be an effective antioxidant in MDA-MB-231 breast cancer cells and MIA PaCa-2 pancreatic cancer cells [19]. We also evaluated a number of known tubulindestabilising agents [colchicine, 2 and four chalcones (14-17, Figure 5)].…”
Section: Effect Of Pre-treatment With Antioxidants On Cellular Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Prussian staining are shown in Figure 1A, and showed that macrophages could rapidly take up iron ion. Considering that previous studies have shown a relationship between intracellular iron concentration and macrophage polarization,3, 5 we measured the expression of IL‐1ÎČ, IL‐10, TNF‐α, and TGF‐ÎČ with Western blotting (Figure 1B), the result showed expression of IL‐1ÎČ and TNF‐α increased. The results of qRT‐PCR and flow cytometry are shown in Figure 1C,D, and showed that both Fe 2+ and Fe 3+ induced the expression of M1‐associated maker such as TNF‐α, CD86, and iNOS.…”
Section: Resultsmentioning
confidence: 99%
“…ROS mainly include superoxide, hydrogen peroxide, singlet oxygen, ozone, hypohalous acids, and organic peroxides, all of which are byproducts of aerobic metabolism. Levels of ROS are mainly regulated by nonenzymatic antioxidants (eg, α‐tocopherol and glutathione) and antioxidant enzymes (eg, superoxide dismutase and catalase) 5. ROS physiologically regulates the synthesize of some kinds of proteins, such as phosphatase and tensin homologue, epidermal growth factor receptor, protein kinase B, and histone deacetylases,6, 7, 8, 9 and oxidizes DNA to promote transcription 4…”
Section: Introductionmentioning
confidence: 99%